Handbook of Cardiovascular Disease Management in Rheumatoid Arthritis - Semb, Anne Grete; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2017)
This book is a practical and up-to-date review that discusses the impact of traditional cardiovascular risk factors in patients with rheumatoid arthritis, the effect of rheumatoid arthritis disease activity and severity on cardiovascular comorbidity, and the influence of rheumatoid arthritis drug therapy on cardiovascular risk. This title also explores cardiovascular disease as a manifestation of rheumatoid arthritis and highlights the available methods for screening and diagnosing these conditions. Current and emerging therapies to aid clinicians in the daily management of their patients are also featured in this title. Busy healthcare professionals who are looking for a collaborative approach to these conditions will benefit from this comprehensive overview.
Overview of rheumatoid arthritis and mortality in relation to cardiovascular disease -- Non-atherosclerotic cardiac manifestations of rheumatoid arthritis -- Risk factors for cardiovascular disease in rheumatoid arthritis -- Cardiovascular disease risk evaluation -- Pharmacological management of cardiovascular disease in patients with rheumatoid arthritis -- Non-pharmacological interventions for cardiovascular complications in patients with rheumatoid arthritis -- Conclusions. .
Keywords: Medicine; Cardiology; Rheumatology; Medicine & Public Health; Cardiology; Rheumatology